A study on environmental aspects and associated impacts of selected farms management practices / Nur Ezira Ramli - Nur Ezira, Ramli (2011)
Livestock farming contributes the production of food at the expense of environmental degradation on air, water and soil/land. The qualitative study, an initial environmental review (IER) was conducted to identify overall farm operation and management practice via various environmental aspects and associated impacts. The study has identified activities in selected farms with significant impacts on environment are transportation, resource consumption, manure and wastewater management. As observed, two farms have initiated a sustainable and environmentally livestock farming practice by taking consideration on natural resources consumption, animal, waste and impacts to nature. An increase of livestock population with time, a periodically review and assessment on baseline information is proposed in future hence findings might quite different. Other farms operator can adapt a Good Farming Practice (GFP) implemented in two farms determined by the study findings. As recommendation, activities with significant impacts should taken into consideration to mitigate the impacts and proposed modification on any technology used in farm operation so that it meets the economic resources and other aspects of farm producer to achieve sustainable farming in Malaysia.